Mapping the CMB Sky: The BOOMERANG experiment - de Bernardis, P.; Ade, P. A. R.; Artusa, R.; Bock, J. J.; Boscaleri, A.; Crill, B. P.; De Troia, G.; Farese, P. C.; Giacommetti, M.; Hristov, V. V.; Iacoangeli, A.; Lange, A. E.; et al. (arXiv, 1999)
We describe the BOOMERanG experiment, a stratospheric balloon telescope intended to measure the Cosmic Microwave Background anisotropy at angular scales between a few degrees and ten arcminutes. The experiment has been optimized for a long duration (7 to 14 days) flight circumnavigating Antarctica at the end of 1998. A test flight was performed on Aug.30, 1997 in Texas. The level of performance achieved in the test flight was satisfactory and compatible with the requirements for the long duration flight. : 11 pages, 6 figures